On the Distributive Effects of Terms of Trade Shocks : The Role of Non-tradable Goods. (IMF Working Papers; Working Paper, 2010)
We introduce non-tradable goods to the Heckscher-Ohlin-Samuelson (HOS) model to study the distributive effects of terms of trade shocks. We show that the employment of resources in activities producing exclusively for the local market induces a crucial association between domestic spending and factor demand and prices, which is absent in the usual HOS framework. Specifically, in a two-sector economy (producing only exportable and non-tradable goods) there are no redistributive effects of external terms of trade shifts-i.e. no Stolper-Samuelson-type of effect. By extending the model to the domestic production of a third, importable good, we show that distributional tensions arise. Distributional conflicts occur within urban labor groups (skilled vs. unskilled) and not only between the "traditional" rural vs. urban factors. Finally, export taxes are imposed to re-distribute the effects of external shocks. We show that the ability of the government to cushion the impact of the terms of trade shift on the economy's income distribution depends crucially on the use of the tax revenues.